Rancang bangun mesin CNC router 3 axis dengan penggerak ballscrew untuk kerajinan acrylic - Pancarana, I Dewa Made; Putrawan, I Made Agus; Gunawan, I Made Rai (Rekayasa Material, Manufaktur dan Energi, 2025)
This research aims to design, manufacture and test a 3-axis CNC router machine with a ballscrew drive that can process acrylic into an artistic craft that has accurate, precise, neat and effective dimensions. In this research, a design was carried out to design a 3 axis CNC router machine with a ballscrew drive that suits the needs of medium and large scale industries. The working principle of a 3 axis CNC router machine with a ballscrew drive is to create a design using CAD or CAM software, then the design is converted to G-code (machine code), so that the machine can work according to G-code coordinates. The results of this research include design and construction which includes design designs, design calculations, manufacturing processes, and results of the accuracy of using acrylic materials. The results of the design and construction of a 3 axis CNC router machine with a ballscrew drive, namely a cutting work area of 800 mm x 600 mm x 100 mm, using a Breakout board controller as a controller, using a PC or laptop to find out the MDI movement of G-code coordinates. The cutting results of spindle rpm 6000, 8000, and 10,000 with varying feed rates will affect the roughness of the workpiece cutting results. The conclusion from varying the feed rate is: the greater the feed rate in units (mm/minute), the rougher the cutting results. , and vice versa, if the feed rate is smaller, the results of cutting the workpiece will be smoother.